(NwOKALXNYE CIKLYs - (NrOBERT {UMANs ((NmOSKWAs (NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2023)
(NvANR WOKALXNOGO CIKLA W TWOR^ESTWE rOBERTA {UMANA (B(181-1856) (NPRETERPEL ZNA^ITELXNU@ \WOL@CI@(B,s
Keywords: (NwOKALs